Effect of high intensity interval training and use of Echium amoenum on serum ferritin and CRP levels in overweight and obese women - Maryam Nasri; Farzaneh Taghian (Mashhad University of Medical Sciences, 2020)
Introduction: During obesity, inflammatory markers such as ferritin and C-reactive protein are increased, which is a major mechanism of atherosclerosis and insulin resistance. Regular exercise and medication can reduce these factors and reduce the risk of chronic diseases. This study was performed with aim to compare the effect of 12 weeks of high intensity interval training (HIIT) and use of borage (Echium amoenum L.) on serum CRP and ferritin levels in overweight and obese women. Methods: This randomized clinical trial study was performed on 40 overweight and obese women in 2018. The subjects were randomly divided into four groups of 10 cases in each group (Exercise-Supplement, Exercise, Supplement and Control). Blood samples were collected and analyzed before and after 12 weeks to measure the levels of CRP and ferritin. A high intensity interval training program (85-95% of maximal heart rate) was performed three times a week for 12 weeks, and groups that used Echium amoenum daily received 4 g dissolved in 250 ml of water, for 12 weeks. Data were analyzed by SPSS software (version 21) and Paired t-test and covariance tests and Shapirowilk and Levin tests. PResults: After 12 weeks HIT training, serum ferritin levels increased after the intervention compared to the pre-intervention, so that this increase was significant in the training group (p=0.033) and Echium amoenum group (p=0.016), but was not significant in the training-Echium amoenum group (p=0.323) and control group (p=0.612). Also, CRP decreased after the intervention compared to the pre-intervention, so that this decrease was significant in the training group (p=0.05) and Echium amoenum group (p=0.001), but was not significant in the training-Echium amoenum group (p=0.196) and control group (p=0.571). Conclusion: Performing severe intermittent exercise along with use of Echium amoenum supplementation by reducing CRP and increasing serum ferritin level can improve the complications and diseases caused by obesity. It has also had an impact on general obesity.